Setipiprant for Androgenetic Alopecia in Males: Results from a Randomized, Double-Blind, Placebo-Controlled Phase 2a Trial - DuBois J; Bruce S; Stewart D; Kempers S; Harutunian C; Boodhoo T; Weitzenfeld A; Chang-Lin JE (Dove Medical Press, 2021)
Janet DuBois,1 Suzanne Bruce,2 Daniel Stewart,3 Steven Kempers,4 Christy Harutunian,5 Terry Boodhoo,5 Amy Weitzenfeld,6 Joan-En Chang-Lin5 1DermResearch, Inc., Austin, TX, USA; 2Suzanne Bruce and Associates, PA, Houston, TX, USA; 3Midwest Center for Dermatology & Cosmetic Surgery, Clinton Township, MI, USA; 4Associated Skin Care Specialists, Fridley, MN, USA; 5Allergan Aesthetics, an AbbVie Company, Irvine, CA, USA; 6Allergan Aesthetics, an AbbVie Company, Madison, NJ, USACorrespondence: Joan-En Chang-LinClinical Development, Allergan Aesthetics, an AbbVie Company, 2525 Dupont Dr, Irvine, CA, 92612, USATel +1 714-246-4680Email joanen.lin@abbvie.comPurpose: To evaluate oral setipiprant versus placebo for scalp hair growth in men with androgenetic alopecia (AGA).Patients and Methods: Males aged 18 to 49 years with AGA were enrolled in a double-blind, multicenter, 32-week, phase 2a trial; randomized to twice-daily (BID) 1000-mg (2× 500 mg for a total daily dose of 2000 mg) setipiprant tablets or placebo for 24 weeks; and assessed at weeks 4, 8, 16, and 24, with a week 32 follow-up. The study initially included a finasteride 1-mg once-daily group, removed by protocol amendment. Changes from baseline to week 24 in target area hair count (TAHC) and blinded Subject Self-Assessment (SSA) of target area photographs were coprimary efficacy endpoints. Hair growth was also evaluated using blinded Investigator Global Assessment (IGA). Safety assessments included adverse events (AEs) and clinical laboratory tests. Analysis of covariance models were used to test statistical significance for TAHC, SSA, and IGA. Data were summarized without statistical analysis for finasteride.Results: Randomized subjects (N=169) included 74 placebo, 83 setipiprant, and 12 finasteride subjects; 117 (69.2%) and 113 (66.9%) subjects completed week 24 and 32 visits, respectively. Treatment groups had similar baseline characteristics. Neither coprimary efficacy endpoint was met. At week 24, TAHC and SSA findings indicated no hair growth improvements with setipiprant versus placebo. Setipiprant also did not improve hair growth versus placebo per the IGA. Treatment-related AEs, all mild or moderate in severity, occurred in 12.3%, 25.9%, and 25.0% of the placebo, setipiprant, and finasteride groups, respectively. Two treatment-emergent serious AEs (TESAEs), cellulitis and multiple sclerosis, were reported in the placebo group, both unrelated to treatment. No TESAEs were reported with setipiprant or finasteride.Conclusion: Setipiprant 1000 mg BID was safe and well tolerated but did not demonstrate efficacy versus placebo for scalp hair growth in men with AGA.Keywords: scalp, hair loss, hair growth and development, prostaglandin receptors